Pengaruh Budaya Organisasi dan Motivasi Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening Studi Kasus Pada PT Karya Mekar Dewatamali di Kota Jombang - Deccasari, Dwi Danesty (STIE Malangkucecwara, 2019)
The purpose of this study is to examine and analyze the influence of organizational culture and motivation on employee performance, examine and analyze organizational culture and motivation on employee performance through job satisfaction as an intervening variable. This research was conducted at PT Karya Mekar Dewatamali Jombang. The number of respondents as many as 60 respondents. This study used a purposive sampling technique. It can be concluded that simultaneously or together, Organizational Culture (X1), Motivation (X2) and Job Satisfaction (Z) on Performance (Y). Moreover, this research also shows that each variable has an influence on the performance variable partially. It states that a good organizational culture will directly make employee performance good without paying too much attention to job satisfaction. The effect of Motivation variable (X2) on Employee Performance (Y) directly is 0.529 while the indirect effect is 0.054. And also, the direct influence of Motivation on Employee Performance is greater than the indirect effect (through intervening variables of job satisfaction).